Will Tanner: Evil Never Sleeps - Book 4 - Johnstone, William W.; Johnstone, J. A.; Kensington Publishing Corporation (New York, New York : Pinnacle Books/Kensington Publishing Corp., 2018)
"U.S. Deputy Marshal Will Tanner sets off into Oklahoma Territory pursuing a bank robber unaware that notorious cattle rustler Jebediah Cotton has sent his five remaining sons and a cold-hearted brother-in-law after Tanner to avenge the death of Cottons youngest son"--
Keywords: United States marshals -- Fiction; Outlaws -- Fiction; Revenge -- Fiction; Frontier and pioneer life -- Fiction; Robbers and outlaws -- Fiction; Oklahoma; Fiction; Western fiction